Interaction between dietary selenium intake and age on severe headache or migraine in the United States: a population-based study - Yu, Xinping; Wu, Lanxiang; Zheng, Heqing; Wu, Wei; Tian, Sheng (Frontiers in Nutrition, 2025)
BackgroundStudies have shown that an antioxidant diet is a protective factor against migraine. However, the association between selenium, an important antioxidant consumed from the diet, and migraine has received little attention. The aim of this study was to explore the relationship between dietary selenium intake with migraine, with particular interest in age differences.MethodsThis study based on cross-sectional data from people who took part in the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2004. The multiple logistic regression model was applied to examine the association between selenium intake and migraine, and subgroup analyses were performed. Non-linear associations were explored with restricted cubic spline (RCS) models.ResultsThe study included a total of 9,849 adults aged 20 years and older. Compared with individuals with lowest selenium intake Q1 (≤59.4 ug/day), the adjusted OR values for selenium intake and migraine in Q2 (59.41–82.70 ug/day), Q3 (82.71–106 ug/day), Q4 (106.01–143.16 ug/day), and Q5 (≥143.17 ug/day) were 0.82 (95% CI: 0.64–1.05), 0.99 (95% CI: 0.77–1.26), 0.74 (95% CI: 0.54–0.99), and 0.68 (95% CI: 0.48–0.97), respectively. Sensitivity analyses showed a robust association between them. Our findings also suggested an interaction between age and selenium intake (p for interaction = 0.04). Additionally, the relationship between selenium intake and migraine in adults with 20–50 years was L-shaped. The OR of developing migraine was 0.97 (95% CI: 0.94–0.98) in individuals with selenium intake ≥101.9 ug/day in adults with 20–50 years.ConclusionA higher dietary selenium intake is significantly associated with a decreased prevalence of migraine, and age can modify the association between them. Therefore, the present study indicate that an appropriate intake of selenium-rich foods in adults aged 20–50 years may prevent migraines.